Implications of the Creditors' Influence on Corporate Decisions - Carsten S. Ruhnke (Junior Management Science (JUMS), 2022)
Debt-financing potentially causes frictions in firms, as the creditors represent an additional group of stakeholders creating conflicts of interest with other stakeholders. This raises the question how corporate performance is affected by the presence of creditors. Could it be in the firms' interest to let the creditors influence corporate decisions? In order to answer these questions, three theoretical models, depicting the influence of creditors on firms in the principal-agent-context, are analyzed, compared and discussed. Based on that, a model that combines and extends their assumptions is developed. The results show that it might be preferable to let the creditors influence the firm's decisions either permanently or at least in some situations. Also, firms should establish a trustworthy relationship with the creditors in order to minimize the costs due to information asymmetries. Overall, creditors should not be seen as a source of conflict and cost factor but rather as a strategic factor that enables firms to make optimal use of their information and thus, to create a sustainable competitive advantage.
Keywords: 650; Debt contracts; creditor influence; corporate performance; corporate governance; agency theory